Performance of Environmental T-shape Noise Barriers Covered with Primitive Root Diffusers - MONAZZAM, Mohammad Reza; NADERZADEH, Mahdiyeh; NASSIRI, Parvin; FARD, Samaneh Momen Bellah (Archives of Acoustics, 2010)
There is a considerable increase in the use of noise barriers in recent years. Noise barriers as a control noise solution can increase the insertion loss to protect receivers. This paper presents the results of an investigation about the acoustic efficiency of primitive root sequence diffuser (PRD) on an environmental single T-shape barrier design. A 2D boundary element method (BEM) is used to predict the insertion loss of the tested barriers. The results of rigid and with a different sequence diffuser coverage are also predicted for comparison. Employing PRD on the top surface of T-shape barrier has been found to improve the performance of barriers in comparison with the use of rigid and QRD coverage at the examined receiver locations. It has been found that decreasing the design frequency of PRD shifts the frequency effects towards lower frequencies, and therefore the overall A-weighted insertion loss is improved. It was also found that using wire mesh with reasonably efficient resistivity on the top surface of PRD improves the efficiency of the reactive barriers; however utilizing wire meshes with flow resistivity higher than the specific acoustic impedance of air on the PRD top of a diffuser barrier significantly reduces the performance of the barrier within the frequency bandwidth of the diffuser. The performance of a PRD covered T-shape barrier at 200 Hz was found to be higher than that of its equivalent QRD barriers in both the far field and in areas close to the ground. The amount of improvement compared made by PRD barrier compared with its equivalent rigid barrier at far field is about 2 to 3 dB, while this improvement relative to the barrier model "QR4" can reach up to 4-6 dB.